2016
DOI: 10.1128/aac.02014-15
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing and Comparative Analysis of Sequential Outbreaks Caused by Multidrug-Resistant Acinetobacter baumannii at a Large Academic Burn Center

Abstract: f Next-generation sequencing (NGS) analysis has emerged as a promising molecular epidemiological method for investigating health care-associated outbreaks. Here, we used NGS to investigate a 3-year outbreak of multidrug-resistant Acinetobacter baumannii (MDRAB) at a large academic burn center. A reference genome from the index case was generated using de novo assembly of PacBio reads. Forty-six MDRAB isolates were analyzed by pulsed-field gel electrophoresis (PFGE) and sequenced using an Illumina platform. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 53 publications
1
35
0
2
Order By: Relevance
“…878 potential pathogens were recovered from these 774 patients; 298 (5%) had 1 potential pathogen isolated, 164 (3%) had 2 potential pathogens isolated, 97 (2%) had 3 potential pathogens isolated, and 215 (4%) had 4 or more potential pathogens isolated. Of note, two outbreaks with Acinetobacter baumannii occurred in the time periods 9/2007 to 4/2008 and 1/2009 to 9/2010 15 .…”
Section: Resultsmentioning
confidence: 99%
“…878 potential pathogens were recovered from these 774 patients; 298 (5%) had 1 potential pathogen isolated, 164 (3%) had 2 potential pathogens isolated, 97 (2%) had 3 potential pathogens isolated, and 215 (4%) had 4 or more potential pathogens isolated. Of note, two outbreaks with Acinetobacter baumannii occurred in the time periods 9/2007 to 4/2008 and 1/2009 to 9/2010 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Whole-genome sequencing (WGS), an emerging tool for advanced molecular epidemiological investigations involving MDR organisms, allows identification of extended resistance and virulence genotypes and elucidation of transmission routes (7)(8)(9)(10)(11)(12)(13). Recently, WGS-based phylogenetic analyses of E. coli ST131 strains identified a CTX-M-15-associated sublineage, designated H30Rx, within ST131-H30R, which is the fluoroquinoloneresistant subset within ST131-H30 (11).…”
mentioning
confidence: 99%
“…It is important to stress that these mutations have never been reported to induce polymyxins resistance in accordance to the phenotypic susceptibility tests (MIC ≤ 1 mg/ml). [18,19] Sulfonamide resistance in gram-negative bacteria is dependent on genes encoding dihydropteroate-synthase sul1 and sul2. [32] In our analysis we found that both ST195 isolates are characterized by the sul2 sulphonamide resistance determinant, while the ST281 strain presented the sul1 gene.…”
Section: Resistomamentioning
confidence: 99%
“…[16] To trace HAI it is necessary to use the best high resolution typing approach that unequivocally identifies Acinetobacter species and their clonality, in order to search for the index case and to define the strains relatedness to avoid nosocomial cross transmission. [17][18][19] This study described the use of whole genome sequencing (WGS) by Ion Torrent Personal Genome Machine to analyze Acinetobacter-calcoaceticusbaumannii complex strains isolated in a possible outbreak occurring in a Intensive Care Unit of a pediatric hospital. De novo assembled sequences from 13 strains were analyzed to define strains clonality and Resistoma.…”
Section: Introductionmentioning
confidence: 99%